Peningkatan Kemampuan Literasi Numerasi Siswa SMP Swasta Islam Terpadu Karakter Anak Shalih Kota Padang - Haripamyu Haripamyu; Noverina Alfiany; Arrival Rince Putri; Susila Bahri; Monika Rianti Helmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Numerical literacy is an ability that requires an understanding of basic mathematical concepts and skills. Private Integrated Islamic Junior High School (SMPS IT)